PROSEDUT AUDIT KAS DAN SETARA KAS PADA PT. XYZ OLEH KAP KANAKA PURADIREDJA, SUHARTONO - Cahaya Sifa Mutiara (2023)
Kanaka Puradiredja Public Accounting Firm, Suhartono is a PAF that has been authorized by the Minister of Finance and registered with the Financial Services Authority (FSA) to provide general audit services, such as auditing financial reports for one of PAF Kanaka Puradiredja's clients, Suhartono, namely PT. XYZ, which is active in the food and beverage industry. Cash and cash equivalents are essential for businesses because they are highly liquid assets that are used in practically every transaction. currency and currency equivalents have the potential for fraud and misuse because of their nature. As a result, it is essential to have an independent auditor examine the cash and cash equivalents disclosed in the financial statements. The purpose of this report is to ascertain how PT. XYZ audits its cash and financial equivalents. According to the audit's findings, all cash and cash equivalents were fairly recorded.